Association Between Systemic Inflammation and Lipid Metabolism in the Development of Preeclampsia - Gojković, Tamara; Ardalić, Daniela; Banjac, Gorica; Vekić, Jelena; Zeljković, Aleksandra; Munjas, Jelena; Miljković-Trailović, Milica; Jovičić, Snežana; Sarić Matutinović, Marija; Spasojević-Kalimanovska, Vesna; Miković, Željko; Stefanović, Aleksandra (Archives of Pharmacy, 2025)
Preeclampsia (PE) is a pregnancy complication marked by hypertension (≥ 140/90 mmHg) and proteinuria (≥ 300 mg/24 h), with an unclear pathogenesis involving inflammation and dyslipidemia. This study aimed to longitudinally examine changes in lipid status parameters and inflammatory markers in pregnant women at high risk for PE and those who developed PE. Among 91 women, 20 developed PE (PE group), and 71 were high-risk (HR group). Both groups were monitored at four points: T1-first, T2-, T3-third trimester, and T4-pre-delivery. Lipid markers (triglycerides (TG), total cholesterol (TC), HDL-C, LDL-C, apolipoproteins A-I and B-100) and inflammatory markers (high-sensitivity C-reactive protein (hsCRP), resistin, serum amyloid A (SAA), and macrophage chemotactic protein-1 (MCP-1)) were assessed. Results showed significantly higher TG, resistin, and MCP-1 concentrations in the PE group compared to the HR group at T1 (p < 0.05, p < 0.01, p < 0.01, respectively). During pregnancy, both groups exhibited increases in TG, TC, LDL-C, SAA, and MCP-1 (p < 0.001), while HDL-C and resistin increased only in the HR group (p < 0.001). PE development is associated with atherogenic lipid changes, characterized by hypertriglyceridemia and no increase in HDL-C, with elevated SAA potentially diminishing HDL’s protective role.
Keywords: preeclampsia; high-risk pregnancy; lipid profile; inflamation